(untitled) (Acta Scientiarum. Biological Sciences, 2018)
Albizia niopoides (Bentham) Burkart, known as farinha seca, is an arboreal, deciduous and pioneer plant that can be found in the semi-deciduous forest in the Paraná basin. The study on the germination and growth of the plant is fundamental for better knowledge about the establishment and regeneration of the species. Aiming to verify the germination of A. niopoides and subsequent growth, green seeds and brown seeds were germinated in a germination chamber and growth parameters were evaluated at 60, 90, and 180 days after transplanting (DAT) in a greenhouse. There was no significant difference in germination percentage between green and brown seeds. However, lower levels of mean germination times and higher levels of germination speed index were observed for brown seeds. At 180 DAT, plants showed higher shoot dry mass, root dry mass, total dry mass, number leaves and height, with no significant difference between 60 and 90 DAT for total dry mass, root dry mass and root length. The values of stem height/diameter and Dickson quality index, associated to the other growth parameters, indicate quality of the seedlings for field planting at 180 DAT.